Correspondence from Honey Toda to Betty Salzman, July 7, 1944 - Honey Toda::::::author:::
Personal letter describing school and life in Washington, DC, including attendance at the Cavalcade of Freedom show, and asking about friends, including two who may have been at an incarceration camp that she describes as being perhaps near Tahoe.